Odpowiedzi

Najlepsza Odpowiedź!
2010-01-08T21:38:45+01:00
A)
5p-2r=21 / *3
3p+5r=-6 /*(-5)

15p-6r=63
-15p-25r=30
____________
-31r=93/ /(-31)
r=-3

5p-2r=21 /*5
3p+5r=-6 /*2

25p-10r=105
6p+10r= -12
____________
31p= 93/ /31
p=3
r=-3

b)
2x - 3y = 10 /*5
5x + 5y = 0 /*(-2)

10x-15y=50
-10x-10y=0
____________
-25y=50/ /(-25)
y=-2

2x - 3y = 10 /*5
5x + 5y = 0 /*3

10x-15y=50
15x+15y=0
____________
25x=50 / /25
x=2
y=-2

c)
4x + 5y = 12,3 /*3
3x - 2y = -4 /*(-4)

12x+15y=36,9
-12x+8y=16
___________
23y=52,9 //23
y=2,3

4x + 5y = 12,3 /*2
3x - 2y = -4 /*5

8x+10y=24,6
15x-10y=-20
_____________
23x= 4,6 / /23
x=0,3
y=2,3

2010-01-08T21:40:48+01:00
A) 5p - 2r = 21//*(-3)
3p + 5r = -6//*(5)
-15p +6r = - 63
15p +25=-30
31r=-33/:31
r= - 33/31
5p- 2 *(- 33/31)= 21
5p +66/31=21
5p=21-66/31
5p=585/31//:5
p=117/31



b) 2x - 3y = 10//*(-5)
5x + 5y = 0//*2
-10x + 15y = - 50
10x +10y= 0
25y=-50//25
y=-2
2x - 3*(-2)=10
2x+6=10
2x=10-6
2x=4//:2
x=2


c) 4x + 5y = 12,3//*2
3x - 2y = -4 //*5
8x +10y = 24,6
15x - 10y = - 20
23x=-4,6/:23
x=- 0,2
3*(-0,2) - 2y=-4
- 0,6- 2y=-4
-2y=-4+0,6
-2y=-3,4//:(-2)
y=1,7
2010-01-08T21:45:24+01:00
A)5p - 2r=21 razy 3
3p + 5r= -6 razy -5
15p - 6r=63
-15p - 25r=30
-33r=99 podzielić na (-33)
r= -3
3p+5r=-6
r=-3
3p-15=-6 dodać 15 3p=9 podzielić na 3
p=3
b) 2x-3y=10 razy 5
5x+5y=0 razy -2
10x-15y=50
-10x-10y=0
-25y=50 podzielić(-25)
y= -2

y=-2
5x+5y=0
y=-2
5x-10=0 dodać 10
y=-2
5x=10 podzielić na 5
y=-2
x=2

c) 4x+5y=12.3 razy 2
3x-2y=-4 rzay 5
8x+10y=24.6
15x-10y=-20
23x=4.6 podzielić na 23
x=0.2
3x-2y=-4
x=0.2
0.6-2y=-4 odjąc 0.6
x=0.2
-2y=-4.6 podzielić na( -2)
x=0.2
y=2.3


















1 5 1